Development of biomimetic microengineered hydrogel fibers for tendon regeneration - Costa-Almeida, R. (2015)
Musculoskeletal diseases are one of the leading causes of disability worldwide. Tendon injuries are responsible for substantial morbidity, pain and disability. Tissue engineering strategies aim at translating tendon structure into biomimetic materials. The main goal of the present study is to develop microengineered hydrogel fibers through the combination of microfabrication and chemical interactions between oppositely charged polyelectrolytes. For this, methacrylated hyaluronic acid (MeHA) and chondroitin sulfate (MeCS) were combined with chitosan (CHT). Hydrogel fibers were obtained by injecting polymer solutions (either MeHA or MeHA/MeCS and CHT) in separate microchannels that join at a y-junction, with the materials interacting upon contact at the interface. To evaluate cell behavior, human tendon derived cells (hTDCs) were isolated from tendon surplus samples during orthopedic surgeries and seeded on top of the fibers. hTDCs adhered to the surface of the fibers, remaining viable, and were found to be expressing CD44, the receptor for hyaluronic acid. The synthesis of hydrogel fibers crosslinkable through both physical and chemical mechanisms combined with microfabrication technology allows the development of biomimetic structures with parallel fibers being formed towards the replication of tendon tissue architecture.